Prevalence of Hepatitis B and Hepatitis C Viral Infections and Their Associated Factors Among Diabetic Patients Visiting in Lahore - Riaz Hussain; Muhammad Haroon; Tasra Bibi; Romail Khokhar; Sidra Iqbal (Journal of Health, Wellness and Community Research, 2025)
Background: Diabetes mellitus is increasingly recognized as a risk factor for hepatitis B (HBV) and hepatitis C (HCV), yet the burden and correlates of these viral infections among diabetic patients in Lahore remain underexplored. Objective: This study aimed to determine the prevalence of hepatitis B and C viral infections among diabetic patients in Lahore and to identify key associated factors, including glycemic control and demographic variables, to inform targeted prevention strategies. Methods: A cross-sectional observational study was conducted among 103 adult diabetic patients (type 1 and type 2) at a tertiary care hospital in Lahore, employing systematic random sampling. Inclusion required age ≥18 years, confirmed diabetes, and HbA1c ≥6.5%, while patients with severe comorbidities or prior hepatitis treatment were excluded. Data were collected using structured interviews, medical record reviews, and laboratory assessment of HBsAg and anti-HCV via ELISA, confirmed by PCR when available. Glycemic status was measured using certified HbA1c assays. Statistical analysis was performed using SPSS version 28.0, with chi-square tests, t-tests, and logistic regression; ethical approval was secured in accordance with the Helsinki Declaration. Results: HBV prevalence was 43.69% and HCV prevalence was 21.36%. Poor glycemic control (HbA1c ≥8.5%) was independently associated with higher odds of both HBV (OR: 2.45, p = 0.001) and HCV (OR: 3.12, p < 0.001), while males consistently exhibited greater infection rates across strata. Conclusion: Diabetic patients in Lahore exhibit high rates of hepatitis B and C, particularly those with poor glycemic control and males, underscoring the need for routine viral screening, vaccination, and aggressive metabolic management to reduce infectious and hepatic complications in this population.
Keywords: Hepatitis B, Hepatitis C, Diabetes Mellitus, Glycemic Control, Prevalence, Risk Factors, Lahore